Strategi Guru Dalam Mengembangkan Keterampilan Kolaborasi (Collaboration) Siswa Kelas VI Di Sekolah Dasar - Lelva Dianisa; Maryono Maryono; Hendra Budiono (Jurnal Tunas Pendidikan, 2024)
This research aims to describe teachers' strategies in developing collaboration skills for sixth grade students in elementary schools. This research was conducted at SD Negeri 1/IV Jambi City from March 2023 to May 2023. Research data was obtained by conducting observations, interviews and documentation. Data collection aims to see teachers' strategies in developing collaboration skills for class VI students at SD Negeri 1/IV This research uses a qualitative approach with a phenomenological type of research. The subjects of this research were teachers and students of class VI A SD Negeri 1/IV Jambi City. The object of this research is the teacher's strategy in developing collaboration skills for sixth grade elementary school students. Data collection techniques include observation, interviews and documentation. The data obtained was then analyzed using analytical techniques, the first stage of data reduction, the second stage of data presentation, and the third stage of drawing conclusions. The results of the research show that the teacher's strategy in developing collaboration skills is the planning stage: (1) planning basic competencies and indicators of competency achievement (2) planning learning objectives and (3) preparing the learning media that will be used. Implementation stage (1) uses a learning model project based laerning (2) using the discussion method (3) assigning tasks/roles to the group (4). divide into small groups.